KERJASAMA PERDAGANGAN INDONESIA - INDIA DALAM MENINGKATKAN EKSPOR KOMODITAS REMPAH - Robby Nugraha, Try Yoga (Jurnal Manajemen, Akuntansi, Ekonomi, 2023)
This study tries to analyze the effect of international trade and determine the effectiveness and efficiency of an agreed cooperation in this case regarding export activities or trade cooperation between Indonesia and India. Which is related to the continuation of good relations between countries, namely in terms of having an impact between countries and meeting needs and also bilateral relations between the two countries. Given that India is the third main destination country for Indonesian spice exports. Collection and analysis in this study using the method of literature study.